Heartwood/Sapwood Characteristics of Populus euphratica Oliv. Trunks and Their Relationship with Soil Physicochemical Properties in the Lower Tarim River, Northwest China - Tongyu Chen; Tayierjiang Aishan; Na Wang; Ümüt Halik; Shiyu Yao (Plants)
The characteristics of heartwood and sapwood not only reflect tree growth and site quality but also provide insights into habitat changes. This study examines the natural Populus euphratica Oliv. forest in the Arghan section of the lower Tarim River, comparing the heartwood and sapwood characteristics of P. euphratica at different distances from the river, as well as at varying trunk heights and diameters at breast height (DBH). The objective was to examine the correlation between these characteristics and the physicochemical properties of the soil to better understand the ecological response strategies of P. euphratica in arid environments. Results indicated that heartwood radius, sapwood width, sapwood area, and heartwood moisture content decreased with increasing trunk height, following the pattern: 0.3 m > 0.8 m > 1.3 m. In contrast, heartwood density increased as trunk height increased. Most of the heartwood and sapwood indicators increased with larger tree diameters. In the case of P. euphratica with a DBH of less than 45 cm, the difference in moisture content between heartwood and sapwood was not significant (p > 0.05) at heights of 0.3 m and 0.8 m. However, at a height of 1.3 m, the difference was significant (p < 0.05). Soil analysis revealed that factors such as total nitrogen, available potassium, and water content significantly influenced the physical characteristics of P. euphratica heartwood and sapwood across different sites. Redundancy analysis (RDA) further demonstrated that total nitrogen, available phosphorus, and soil moisture were significantly correlated with the physical properties of P. euphratica heartwood and sapwood, further validating the critical role of soil nutrients in shaping the wood characteristics of P. euphratica. These findings highlighted the specific adaptations of P. euphratica in the lower Tarim River to the arid desert environment, reflected in the observed relationships between soil conditions and the physical characteristics of heartwood and sapwood.